PROSEDUR PENETAPAN BANTUAN STIMULAN PERUMAHAN SWADAYA PERSPEKTIF FIQIH SIYASAH DUSTURIYAH (Studi Kasus Di Jorong Buluh-Kasok Kenagarian Padang Air Dingin Kecamatan Sangir Jujuan Kabupaten Solok-Selatan) - Srima Yengsi; Sulastri Caniago (Institut Agama Islam Negeri Batusangkar, 2021)
This paper aims to explain the procedure for determining self-help housing stimulant assistance in Jorong Buluh-Kasok Nagari Padang Air Cold, Sangir Jujuan District, Solok-Selatan Regency based on the Minister of PUPR Regulation Number 13/PRT/M/2016 and the Fiqh Siyasah Duturiyah Perspective. The type of research is field research (field research). The data sources of this study consisted of primary data sources, namely the head of the technical team for house renovation in Solok-Selatan Regency, the head of the administrative section of the wali nagari, the head of jorong Buluh-Kasok, community leaders in Jorong Buluh Kasok and secondary data, namely scientific books, research results, legislation related to research and documents. Data collection techniques are interviews and documentation. The data were analyzed using a qualitative descriptive method. This study found that the cause of the mechanism for determining the self-help housing stimulant assistance in Jorong Buluh Kasok was not right on target because there were parties who did not carry out their technically determined duties. Of the three persons in charge and requesting house renovation assistance, namely: the Technical Team for house renovation, the Wali Nagari Padang Air Cold, and Jorong Buluh-Kasok. The party who does not carry out their duties is the technical team for home renovation, where the technical team does not carry out their duties as supervisors for the implementation of home renovation assistance, while in Ministerial Regulation No. and evaluation of the provision of home surgery assistance. Meanwhile, according to Fiqh Siyasah Duturiyah's view of the procedure for determining this self-help housing stimulant assistance, it lies in the task of the executive agency (al-sultah al-tanfidziyah) where the task of the al-sultah al-tanfidziyah institution is to implement the laws and regulations that have been set. , in the principle of fiqh siyasa this is included in the principle of justice where to create justice one must not look at status or position.